Are the effects of internal focus instructions different from external focus instructions given during balance training in stroke patients? A double-blind randomized controlled trial. (February 2019) - Kal, Elmar; Houdijk, Han; van der Kamp, John; Verhoef, Manon; Prosée, Rens; Groet, Erny; Winters, Marinus; van Bennekom, Coen; Scherder, Erik
Objective: This study aimed to assess if external focus instructions result in greater improvements in motor skill and automaticity compared to internal focus instructions in stroke patients. Design: Double-blind randomized controlled trial. Setting: Inpatient stroke rehabilitation unit. Subjects: A total of 63 stroke patients (Meanage  = 59.6 ± 10.7 years; Meandays since stroke  = 28.5 ± 16.6; MedianFunctional Ambulation Categories  = 4). Interventions: Patients were randomly assigned to an internal ( N  = 31) or external ( N  = 32) focus instruction group. Both groups practiced a balance board stabilization task, three times per week, for three weeks. Balance performance was assessed at baseline, and after one and three weeks of practice. Main measures: Primary outcome was the threshold stiffness (Nm/rad) at which patients could stay balanced. Secondary outcomes were patients' sway (root-mean-square error in degrees) at the baseline threshold stiffness under single- and dual-task conditions, and their performance on the Timed Up and Go Test and Utrecht Scale for Evaluation of Rehabilitation. Results: Both groups achieved similar improvements in threshold stiffness (∆= 27.1 ± 21.1 Nm/rad), and single- (∆= 1.8 ± 2.3° root-mean-square error) and dual-task sway (∆= 1.7 ± 2.1° root-mean-square error) after three weeks of practice. No differences were found in improvements in clinical tests of balance and mobility. Patients with comparatively good balance and sensory function, and low attention capacity showed greatest improvements with external focus instructions. Conclusion: External focus instructions did not result in greater improvement in balance skill in stroke patients compared to internal focus instructions. Results suggest that tailoring instructions to the individual stroke patient may result in optimal improvements in motor skill.